AIDS: Access to universal therapy and new strategies - Yglesias Bedoya, Arturo (2009)
A quarter of a century has elapsed since the first occurrence of human immunodeficiency virus (HIV) infections and its dramatic well-described consequences. Enormous amounts of money have been spent in research, and many important advances in diagnosis and therapy have taken place. Nowadays, strategies against HIV infection do not only require a global and coherent response, but also current policies must be strengthened, and new policies msut be designed so that there may be a better interaction between every community affectedby HIV/AIDS, particularly in developing countries, which are by far the most affected areas by this pandemic.